2016
DOI: 10.1039/c5gc02576a
|View full text |Cite
|
Sign up to set email alerts
|

Facile extraction of cellulose nanocrystals from wood using ethanol and peroxide solvothermal pretreatment followed by ultrasonic nanofibrillation

Abstract: Cellulose nanocrystals (CNCs) were successfully extracted from wood flour by a two-step process that comprised ethanol and peroxide solvothermal pretreatment and an ultrasonic disintegration process.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
118
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 207 publications
(120 citation statements)
references
References 44 publications
2
118
0
Order By: Relevance
“…Previous works reporting CNC production by acid methods applied to sources of cellulose including eucalyptus showed the advantage of the enzymatic method and found similar ranges of length and diameter, with L = 175–142 nm and D = 11–15 nm for eucalyptus cellulose, L = 100–300 nm and D = 3–10 nm for waste paper, and L = 500 nm and D = 1–9 nm for wood . However, it is important to emphasize that obtaining CNC using enzymatic hydrolysis alone is innovative.…”
Section: Resultsmentioning
confidence: 92%
“…Previous works reporting CNC production by acid methods applied to sources of cellulose including eucalyptus showed the advantage of the enzymatic method and found similar ranges of length and diameter, with L = 175–142 nm and D = 11–15 nm for eucalyptus cellulose, L = 100–300 nm and D = 3–10 nm for waste paper, and L = 500 nm and D = 1–9 nm for wood . However, it is important to emphasize that obtaining CNC using enzymatic hydrolysis alone is innovative.…”
Section: Resultsmentioning
confidence: 92%
“…In recent years, ionic liquids such as 1-butyl-3-methylimidazolium hydrogen sulfate (BmimHSO4) have been proposed as a potential hydrolyzing catalyst for cellulose depolymerization process, and the results showed that high crystallinity nanocellulose (95.8%) was isolated successfully from cotton linter model compound (84.4%) via ionic liquid catalyzed hydrolysis process by using BmimHSO4 at 90 o C for 1.5 h (Tan et al 2015). In the same year, a new hydrolysis approach which comprised ethanol and peroxide solvothermal pretreatment followed by ultrasonic process has been developed by Li and his coworkers for isolation of nanocellulose (Li et al 2016). They treated the wood flour with the proposed pretreatment under reaction conditions of 180 o C for 80 min, and the results revealed that the nanocellulose produced had higher crystallinity (79.37%) than raw material (70.72%) (Li et al 2016).…”
Section: Introductionmentioning
confidence: 99%
“…In the same year, a new hydrolysis approach which comprised ethanol and peroxide solvothermal pretreatment followed by ultrasonic process has been developed by Li and his coworkers for isolation of nanocellulose (Li et al 2016). They treated the wood flour with the proposed pretreatment under reaction conditions of 180 o C for 80 min, and the results revealed that the nanocellulose produced had higher crystallinity (79.37%) than raw material (70.72%) (Li et al 2016). In spite of their prolific use, the capital cost for the nanocellulose production is one of the major concerns in the industrial applications.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Wood has been used to build structures such as bridges, house, towers, and furniture from ancient times to present day . Compared with the manufacturing processes of steel, concrete, and other construction materials, wood processing not only reduces the energy consumption but also results in a positive contribution to the carbon footprint due to its green and environmentally friendly characteristics . Despite these attractive features, wood still faces challenges in the modern construction industry because of its high fire risk.…”
Section: Introductionmentioning
confidence: 99%